2012
DOI: 10.1590/s0102-311x2012000100013
|View full text |Cite
|
Sign up to set email alerts
|

Different equations for determining height among the elderly: the Bambuí cohort study of aging

Abstract: The aim of this study was to compare measured height with estimates of height derived from equations using half arm-span measurements and assess how this affects the calculation of the body mass index (BMI) among elderly individuals. Direct height measurements of a subsample of elderly individuals from the baseline sample of the Bambuí Project were compared with estimates of height derived from equations proposed by Bassey and the WHO. The data was analyzed using the McNemar test, Lin concordance correlation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…The WHO ( 17 ) recommends that the WHO equation should be used as a universal equation to calculate estimated height. However, in the current study the WHO equation was identified to be the least predictive height estimation method in the calculation of true height as it statistically significantly underestimated height for all race groups of both genders ( 11 , 27 ) . On the other hand, the WHO-adjusted equation agreed sufficiently with SS and was predictive of true height in the study sample, especially Black African males and Indian females.…”
Section: Discussionmentioning
confidence: 58%
“…The WHO ( 17 ) recommends that the WHO equation should be used as a universal equation to calculate estimated height. However, in the current study the WHO equation was identified to be the least predictive height estimation method in the calculation of true height as it statistically significantly underestimated height for all race groups of both genders ( 11 , 27 ) . On the other hand, the WHO-adjusted equation agreed sufficiently with SS and was predictive of true height in the study sample, especially Black African males and Indian females.…”
Section: Discussionmentioning
confidence: 58%
“…Por outro lado, a elevação da prevalência de obesidade abdominal nos idosos também é afetada pela redução da estatura com o envelhecimento, já que a altura é denominador dessa medida. A redução da estatura pode se dever a alterações ósseas, como achatamento das vértebras, redução dos discos intervertebrais, cifose dorsal, escoliose, arqueamento dos membros inferiores e/ ou achatamento do arco plantar 42,43 .…”
Section: Variáveisunclassified
“…Standing height is often directly measured using a linear scale. However, among the elderly, physiological and pathological changes including vertebral flattening and fractures, compression and attrition of intervertebral discs, dorsal kyphosis, scoliosis, bowing of legs and flattening of the plantar arch, 5 , 11 and being bedridden lead to inaccurately lowered height measurement that overestimates BMI 12 , 13 and thereby results in discrepant prevalence rates of undernutrition and obesity.…”
Section: Introductionmentioning
confidence: 99%